ALGORITHM FOR FEATURE EXTRACTION FROM EAR IMAGES ON THE BASE OF DISCRETE COSINE TRANSFORMATIONS - Jumayev Turdali Saminjonovich; Mahkamov Anvarjon Abdujabborovich (Web of Journals Publishing, 2024)
This article is about one of the important issues of identifying a person on the basis of biometric parameters, a method of distinguishing features characterizing the image. It is implemented on the basis of discrete cosine transformation of image characteristics. The study was carried out on the image of the auricle of a person.